Harm, compensation and responsability: moral and psychological aspects - Zingeris, Markas (Genocidas ir rezistencija, 2002)
This article discusses the issues of injustice, compensation, and responsibility towards Holocaust victims. Can reparations compensate for the wrongs done? Societal processes such as fair coverage of the Holocaust, the administration of justice, and not so much the courts themselves as their didactic and educational meaning, the commemoration of massacre sites, what guarantees human rights, individual attention and understanding, and simple, human solidarity, also compensate to some extent for the long–lasting dehumanisation process that the survivors have had to undergo.